The Effect of Assessment Strategy on Students’ Character and Creative Thinking Ability in Designing Learning Media - Pantiwati, Yuni; Chamisijatin, Lise; Zaenab, Siti; Sari, Tasya Novian Indah (Jurnal Pendidikan Progresif, 2022)
The Influence of Assessment Strategy on Creative Thinking Ability and Character in Making Learning Media.  Objective: assessment strategy its effect on creative thinking ability and academic character of students in making learning media. Methods: research quasi-experimental method one-group pretest-posttest design. The research was carried out in the Biology Education Study Program of UMM in the odd semester of 2021/2022. The research population is students in the Media and Learning course. Saturated sampling technique and sample of 25 students. The research instrument consisted 6 creative thinking essay questions and an academic character assessment form. Data were analyzed statistically using ANOVA. Findings: the application of the assessment strategy has a significant effect on students' creative thinking skills in making learning media for biological diversity, fungi and inheritance. The assessment strategy used has an influence on the academic character of students. Conclusion: good assessment strategy will encourage educators to determine good teaching strategies and motivate students to learn better so that learning becomes meaningful. Keywords: elaboration, flexibility, fluency, metaphorical thinking, academic character, originality.DOI: http://dx.doi.org/10.23960/jpp.v12.i3.202213